Living Black : Social Life in an African American Neighborhood - Fleisher, Mark S. (Book collections on Project MUSE., 2015)
"Living black breaks the stereotype of poor African American neighborhoods as dysfunctional ghettos of helpless and hopeless people. Despite real and enduring poverty, the community described here -- the historic North End of Champaign, Illinois -- has a vibrant social life and strong ties among generations. But it operates on its own nonjudgmental terms -- teen moms aren't derided, school dropouts aren't ridiculed, and parolees and ex-cons aren't scorned. Mark Fleisher offers a window into daily life in this neighborhood, particularly through the stories of Mo and Memphis Washington, who fight to sustain a stable home for their children, and of Burpee, a local man who has returned to the North End to rebuild his life after years of crime and punishment in Chicago."--Publisher's description.